Correlated Coordination and Redox Activity of a Hemilabile Noninnocent Ligand in Nickel Complexes. Issue 18 (24th March 2014) - Paretzki, Alexa; Bubrin, Martina; Fiedler, Jan; Záliš, Stanislav; Kaim, Wolfgang
Abstract The compound [Ni(QM)2], QM=4, 6‐di‐tert‐butyl‐N‐(2‐methylthiomethylphenyl)‐o‐iminobenzoquinone, is a singlet diradical species with approximately planar configuration at the tetracoordinate metal atom and without any NiS bonding interaction. One‐electron oxidation results in additional twofold NiS coordination (dNiS≈2.38 Å) to produce a complex cation of [Ni(QM)2](PF6) with hexacoordinate NiII and two distinctly different mer‐configurated tridentate ligands. The O, O′‐trans arrangement in the neutral precursor is changed to an O, O′‐cis configuration in the cation. The EPR signal of [Ni(QM)2](PF6) has a very large g anisotropy and the magnetic measurements indicate an S=3/2 state. The dication was structurally characterized as [Ni(QM)2](ClO4)2 to exhibit a similar NiN2O2S2 framework as the monocation. However, the two tridentate (O, N, S) ligands are now equivalent according to the formulation [NiII(QM0)2]2+. Cyclic voltammetry reflects the qualitative structure change on the first, but not on the second oxidation of [Ni(QM)2], and spectroelectrochemistry reveals a pronounced dependence of the 800–900 nm absorption on the solvent and counterion. Reduction of the neutral form occurs in an electrochemically reversible step to yield an anion with an intense near‐infrared absorption at 1345 nm (ε=10400 M−1 cm−1) and a conventional g factor splitting for a largely metal‐based spin (S=1/2), suggesting a [(QM.−)NiII(QM2−)]− configuration with a tetracoordinate metal atom with antiferromagnetic NiII–(QM.−) interactions and symmetry‐allowed ligand‐to‐ligand intervalence charge transfer (LLIVCT). Calculations are used to understand the NiS binding activity as induced by remote electron transfer at the iminobenzoquinone redox system.